2006
DOI: 10.1530/eje.1.02298
|View full text |Cite
|
Sign up to set email alerts
|

Non-functioning pituitary adenoma database: a useful resource to improve the clinical management of pituitary tumors

Abstract: Objective: The long-term outcome of non-functioning pituitary adenoma (NFPA) patients is not clearly established, probably due to the low annual incidence and prolonged natural history of these rare tumors. The aim of this study was to evaluate clinical data at presentation and long-term post-surgery and radiotherapy outcome in a cohort of patients with NFPA. Design and methods: A computerized database was developed using Access 2000 software (Microsoft Corporation, 1999). Retrospective registration of 295 NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
196
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(232 citation statements)
references
References 40 publications
26
196
1
7
Order By: Relevance
“…The slow progressive development of a lesion without functional indicators that would facilitate diagnosis seems to have led to two basic types of complaints among these patients: headache and visual disturbances. These symptoms have also been reported by other patients at the time of diagnosis 20,22 . Visual changes were present in 87.3% of the patients, given that the study population had only been referred to the hospital when they showed large lesions (average size of 3.1 cm).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The slow progressive development of a lesion without functional indicators that would facilitate diagnosis seems to have led to two basic types of complaints among these patients: headache and visual disturbances. These symptoms have also been reported by other patients at the time of diagnosis 20,22 . Visual changes were present in 87.3% of the patients, given that the study population had only been referred to the hospital when they showed large lesions (average size of 3.1 cm).…”
Section: Resultssupporting
confidence: 83%
“…In our sample, this was achieved through reduction of tumor volume and, more exceptionally, tumor exclusion. This difficulty in achieving tumor cure through surgery was also observed in 295 patients with non-functioning tumors, among whom this was achieved in only 35.5% 22 . Recurrence occurred in 19.2% of those who had no residual tumor after a mean of seven years after the surgery and in 58% of those with tumor residues after an average of five years.…”
Section: Pituitary Apoplexymentioning
confidence: 95%
“…Case 1 and 6 with normal level of PRL showed hypogonadotropic hypogonadism without abnormalities in CT or MRI. In the cases of hypopituitarism caused by pituitary mass [27,28] or apoplexy [29,30], gonadotropin is known as one of the pituitary hormones that are impaired early. However, case 1 and 6 showed no abnormalities in the images, supporting the possibility that they might not have shown structural disorder due to xanthogranulomatous infiltration, but might have been reported that interferon α shows direct inhibitory effects on thyroid hormone synthesis, release, and metabolism [39].…”
Section: Hypothalamic-pituitary Imaging In Ecdmentioning
confidence: 99%
“…33 The database was divided into two parts: a principal table, including information about the patient at the time of recruitment, and several follow-up records. Each patient received an identification number, and personal information was available only to principal investigators or coinvestigators.…”
Section: Subjectsmentioning
confidence: 99%